2019
DOI: 10.1016/j.cell.2019.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Lineages with Vaccine-Induced Antigen-Binding Hotspots Develop Broad HIV Neutralization

Abstract: SUMMARY The vaccine-mediated elicitation of antibodies (Abs) capable of neutralizing diverse HIV-1 strains has been a long-standing goal. To understand how broadly neutralizing antibodies (bNAbs) can be elicited, we identified, characterized, and tracked five neutralizing Ab lineages targeting the HIV-1-fusion peptide (FP) in vaccinated macaques over time. Genetic and structural analyses revealed two of these lineages to belong to a reproducible class capable of neutralizing up to 59% of 208 diverse viral stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 108 publications
7
153
0
Order By: Relevance
“…To develop FP-carrier conjugates as immunogens for clinical evaluation, we analyzed the prevalence of FP sequences in the HIV LANL database 34 . The N-terminal 6 residues of FP account for 72% of the FP interface-buried surface area, when complexed with the broadly neutralizing FP-directed antibody N123-VRC34.01 3 , and we observed a similar focus on the N-terminal 6-8 residues of FP in FP-directed HIV-1 neutralizing antibodies elicited in mice and macaques 2,12 . The N-terminal FP residues are variably conserved, with a cumulative frequency of the top 4 most prevalent N-terminal sequences of FP6 (residues 512-517 of Env) utilized by ~65% of the HIV-1 isolates in the LANL database and the top 4 most prevalent N-terminal sequences of FP8 (residues 512-519 of Env) utilized by ~35% of the HIV-1 isolates in the LANL database ( Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…To develop FP-carrier conjugates as immunogens for clinical evaluation, we analyzed the prevalence of FP sequences in the HIV LANL database 34 . The N-terminal 6 residues of FP account for 72% of the FP interface-buried surface area, when complexed with the broadly neutralizing FP-directed antibody N123-VRC34.01 3 , and we observed a similar focus on the N-terminal 6-8 residues of FP in FP-directed HIV-1 neutralizing antibodies elicited in mice and macaques 2,12 . The N-terminal FP residues are variably conserved, with a cumulative frequency of the top 4 most prevalent N-terminal sequences of FP6 (residues 512-517 of Env) utilized by ~65% of the HIV-1 isolates in the LANL database and the top 4 most prevalent N-terminal sequences of FP8 (residues 512-519 of Env) utilized by ~35% of the HIV-1 isolates in the LANL database ( Fig.…”
Section: Resultssupporting
confidence: 67%
“…While FP-carrier protein priming is important for initiating FP-directed responses 12 , Env trimer boosts are also important to mature the responses into potent broad neutralization 1,2,12 . Furthermore, our results suggest that compared to Adjuplex, use of Alum as an adjuvant resulted in slower development of anti-FP responses during the FP8v1-rTTHC priming stage, though these responses continued to develop upon trimer boosting, ultimately yielding similar responses as induced by Adjuplex at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Using the epitope focusing approach, a more recent study showed that the FP-coupled carrier protein immunogens could induce cross-reactive FP-targeted neutralization activities in mice, guinea pigs and NHPs [19,20]. More importantly, mAbs representing the similar neutralization breadth in sera were successfully isolated from several of immunized macaques [21]. These results demonstrate the important roles of bnAbs and possibility to elicit them in NHPs.…”
Section: Introductionmentioning
confidence: 85%
“…One approach to focus the response on the FP is through repeated immunization with 10-100s of copies of the FP displayed on carrier proteins, such as keyhole limpet hemacyanin (KLH), followed by a booster immunization with the Env trimer spike to present the FP in a more native context. This approach has produced encouraging responses in animals with up to 31% and 59% neutralization breadth in mice and macaques, respectively, against panel of diverse HIV isolates [27,28]**. This concept is now being developed for human clinical trials [29].…”
Section: Introductionmentioning
confidence: 99%